Trends in the development of media literacy in Kazakhstan in the context of globalization of the media space - Tahan С.Ш.; Khussainova А.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The article examines the changes caused by the development of digital technologies and the globalization of the media space. Special attention is paid to the development of media literacy as a basic skill of a modern person, necessary for conscious consumption of information and interaction with the digital environment. The purpose of the study is to analyze trends in the development of media education in Kazakhstan and assess the level of media literacy of young people in the context of growing information pressure. The article emphasizes the strategic importance of media literacy in ensuring national security, countering manipulation, propaganda and fake information. The quantitative and analytical data of domestic and foreign research institutes on the use of the Internet and new media by Kazakhstanis are considered. The increasing role of media literacy in the context of the development of new media and the globalization of the media space is emphasized, as well as the risks associated with the low level of media literacy in Kazakh society. The results of a study conducted in a comprehensive school in Astana among students in grades 9-11 to determine the level of media literacy of schoolchildren are presented. A brief overview of the main media educational trends in secondary and higher education institutions, an analysis of the structure and content of media literacy curricula in educational institutions of the country is made. The article focuses on the need to integrate media literacy into educational processes for the harmonious development of the younger generation in the context of the development of digital technologies.